The Semiotics of Love - Danesi, Marcel. author. aut Link
XII, 178 p. 25 illus., 22 illus. in color.
Keywords: The Semiotics of Love brings together work on early symbolism, literary practices, and contemporary communication on the theme of romance and the idea of love to forge an understanding of the semiotic-cultural side of romance. Moving beyond psychological and neuroscientific scholarly analyses of love, Marcel Danesi works to interrogate the cultural constructions of love across societies. This book analyzes romantic love from the general perspective of semiotics—that is, from its more generic interpretive angle, rather than its more technical one. The specific analytical lens used is based on the notion that we convert our feeling structures into sign structures (words, symbols) and sign-based constructions (texts, rituals, etc.), which then allow us to reflect upon something cognitively, rather than just experience it physically and emotionally.